(untitled) (Global Journal of Science Frontier Research, 2017)
Our main focus in this article is to evaluate individually, that is to say, at the level of every country, the impact of climate change on agriculture. The objectif at this level is to set a new world map of the impact of climate change on global agriculture. Our analysis is mainly concerned with impulse response functions as this instrument enables us to synthesize the essential information contained in the dynamics of the estimated VAR system and ECM. Impulse response functions, enabled us to determine the nature of the effects of different shocks on different variables and being based on this instrument one could distinguish 4 large country families on a new global map by type of climate impact.